Atypical severe progressive perioral ulceration due to herpes simplex virus on the background of undiagnosed HIV/AIDS. (2nd July 2019) - Howard, Matthew David; Poon, Flora; Milne, Olivia Jean; Kelmann, Anthony; Chong, Alvin H
Abstract: Perioral ulcerative plaques have a broad list of differential diagnoses. We describe an unusual presentation of chronic progressive perioral ulceration due to herpes simplex type (HSV)‐1 on a background of undiagnosed human immunodeficiency virus infection with acquired immunodeficiency syndrome. Whilst chronic mucocutaneous HSV is an AIDS‐defining condition with both HSV‐1 and HSV‐2 implicated, typical reported cases describe vesicular eruptions rather than perioral ulcerative plaques. This case highlights that common infections may present atypically in immunocompromised individuals and may be a clue to underlying systemic illness.